Effects of anticipation and dual-tasking on lower limb biomechanics while performing change-of-direction tasks in physically active individuals: a systematic review with meta-analysis - Ebner, C.; Granacher, U.; Gehring, D. (Sports Medicine, 2025)
Background: Anterior cruciate ligament (ACL) injuries are highly prevalent in team sport athletes and often occur while performing change-of-direction (COD) tasks in combination with high cognitive demands, such as decision making or divided attention. Given the expanding body of research in this field, an updated literature review is warranted, as the most recent meta-analysis on this topic included original studies published up to November 2020. Objective: The aim of this systematic review was to examine the effects of anticipation and/or dual-tasking on lower limb biomechanics during COD tasks in healthy individuals. Design: Systematic review with meta-analysis. Data Sources: A systematic literature search was conducted in the electronic databases PubMed, Web of Science, CINAHL and SPORTDiscus from inception until February 2024. The included studies examined the effects of anticipation and/or dual-tasking on knee kinetics and kinematics in the frontal and sagittal planes during COD tasks. Methods: A multilevel meta-analysis was performed to aggregate the results of studies comparing unanticipated versus anticipated CODs on lower limb biomechanics. Due to the limited available literature on dual-task versus single-task conditions, this aspect was analyzed qualitatively. Results: The meta-analysis included 17 studies involving 355 individuals from different sports (e.g., soccer, American Football). No statistically significant differences were found between unanticipated and anticipated CODs for knee abduction and flexion moments as well as knee abduction angles (p > 0.05). Significantly higher knee flexion angles were found in unanticipated CODs (SMD = 0.74, 95% CI: 0.30-1.19; p < 0.01). Qualitative analyses of six studies including 171 individuals provided initial evidence for higher knee abduction moments and flexion angles during anticipated CODs while performing a secondary task concurrently. Conclusion: Findings from quantitative and qualitative analyses indicate that anticipation and dual-tasking during COD performance have an impact on injury-related aspects of lower limb biomechanics. Hence, cognitive challenges should be implemented in injury risk screening and preventive strategies. Further studies with high methodological quality are needed to improve the understanding of the biomechanical and cognitive interplay in injury-threatening situations.